The Determinants Of Stock Prices On Goods And Consumption Companies Listed In ISSI (Indonesian Sharia Stock Index) - Yulia, Iis Anisa; Rusli, Abdul Rahman (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
Investment alternative for investors is stock investment in Islamic sharia. The Indonesia Stock Exchange provides a special index that lists stocks in Indonesia that are in accordance with Islamic sharia, namely the Indonesian Sharia Stock Index (ISSI). Based on stock price at sectoral index listed in the Indonesian Sharia Stock Index (ISSI), goods and consumtion sector is decreasing significantly in stock price for three years in 2018-2020. This decrease can be affected by many factors. To know these factors, this research is using fundamental analysis with financial ratio analysis. This research aims to examine the effect of Current Ratio (CR), Debt to Equity Ratio (DER) and Return On Equity (ROE) on stock prices in goods and consumption companies listed on the Indonesian Sharia Stock Index (ISSI). The sampling method is using purposive sampling. The sample used was 28 companies during the 2018-2020 period so the total data processed were 84 observations. The data used is secondary data from the company’s financial statement published at Indonesia Stock Exchange (BEI) in the form of panel data. The analysis technique used is multiple linear regression analysis by using E-Views 10 version data processing application. This research shows that partially Debt to Equity Ratio (DER) and Return On Equity (ROE) significantly affect stock price. While Current Ratio (CR) has no significant effect on stock price. Simultaneously, Current Ratio (CR), Debt to Equity Ratio (DER) and Return On Equity (ROE) has significant effect on stock price.